Solar absorption cooling systems: a review - Mustafa, Ali Abdulqader; Noranai, Zamri; Imran, Ahmed Abdulnabi (Yildiz Technical University Press, Istanbul, Turkey, 2021)
Reduction of the green-house effect can be obtained by reducing the emissions of CO2. One of the technologies that contributes to this purpose is using solar cooling systems. An example of such systems is Lithium Bromide Absorption Chillers-Driven by Hot Water (LiBr/H2O absorption chillers). These chillers are normally powered by solar collectors (ordinary plate or evacuate tubular), which are widely accessible. This paper includes a review of previous experimental and theoretical studies on the effect of single cooling absorption systems. In addition, new proposals regarding the design of the solar collectors, supporting systems for energy and cooling methods will be provided. Furthermore, the present paper also summarizes the major double influence of the cooling absorption systems, add to the two-stage and half-effect absorption coolers. The influence of double cooling absorption systems using solar power could be considered for the buildings with more cooling capacity requirements, but with structure of space restrictions. However, for these cases is important to consider the direct irradiation, which needs high levels. For dry regions with water shortage, half-absorption and two-stage absorption coolers are more suitable. Solar-powered cooling systems designs should follow and incorporate standard rules based on the characteristics of various areas in order to be applicable on a large scale.